Local governance for the environment policy directions in social waste management - Rebullida, Ma. Lourdes G. (2002)
The global community has by now recognized the detrimental consequences of development on the environment. While development has contributed to economic and social progress, it has also led to the deterioration of the environment. Wastes from industrial production, business and commercial activities, and from human consumption account for the pollution and other threats to the quality of air, land, and water. In this context, this study attempts to trace the emergence and characteristics of the urban problematique with wastes and urban environmental management, focusing on solid wastes and solid waste management that have confronted major cities in Asia and other parts of the world. It presents and analyzes international, national, and local cases on policy directions and governance modes to resolve these problems. While citing cases in other countries, the study primarily uses the Philippines as an illustrative case highlighting the burdens for local governance, its problems and challenges.
Keywords: Civil society organizations; Environment and development; Environmental management; Local governance; Solid waste management